2021
DOI: 10.1111/cea.13865
|View full text |Cite
|
Sign up to set email alerts
|

Delayed symptoms and orthostatic intolerance following peanut challenge

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 27 publications
(58 reference statements)
0
7
0
Order By: Relevance
“…The recurrence of anaphylaxis symptoms following initial resolution may be a “biphasic” reaction but can also represent (and be difficult to distinguish from) protracted anaphylaxis with a transient response to adrenaline, or in the case of food-induced reactions, further allergen absorption from the gastrointestinal tract. 75 Historical guidelines have suggested a rate of up to 20% for biphasic reactions, however a recent meta-analysis reported a pooled rate of 4.6% (95% CI 4.0–5.3). 33 A rate of 4.7% has been reported in the European Anaphylaxis Registry.…”
Section: Introductionmentioning
confidence: 99%
“…The recurrence of anaphylaxis symptoms following initial resolution may be a “biphasic” reaction but can also represent (and be difficult to distinguish from) protracted anaphylaxis with a transient response to adrenaline, or in the case of food-induced reactions, further allergen absorption from the gastrointestinal tract. 75 Historical guidelines have suggested a rate of up to 20% for biphasic reactions, however a recent meta-analysis reported a pooled rate of 4.6% (95% CI 4.0–5.3). 33 A rate of 4.7% has been reported in the European Anaphylaxis Registry.…”
Section: Introductionmentioning
confidence: 99%
“…Firstly, participants were eligible for OIT based on a positive history of peanut allergy and positive peanut skin prick test (8 mm) or peanut‐specific IgE (15 kU/L) at screening, rather than failing an OFC at study entry. This approach was selected based on pragmatic reasons including limitations in accessing hospital services to conduct OFC and safety concerns associated with conducting OFC in children with peanut allergies (where symptoms can be delayed following OFC) 18,19 . Furthermore, previous studies have reported high positive predictive value (94%) of using a combination of a positive peanut skin prick test (8 mm) or peanut‐specific IgE (15 kU/L) to determine likely peanut allergy 20–22 .…”
Section: Discussionmentioning
confidence: 99%
“…This approach was selected based on pragmatic reasons including limitations in accessing hospital services to conduct OFC and safety concerns associated with conducting OFC in children with peanut allergies (where symptoms can be delayed following OFC). 18,19 Furthermore, previous studies have reported high positive predictive value (94%) of using a combination of a positive peanut skin prick test (8 mm) or peanut-specific IgE (15 kU/L) to determine likely peanut allergy. [20][21][22] Secondly, we did not employ the use of a control or placebo group.…”
Section: Grade Grade Gradementioning
confidence: 99%
“…However, we recently published data suggesting that vasovagal instability, resulting in orthostatic intolerance, can occur in up to 11% of participants reacting to peanut at a supervised food challenge. 26 This suggests a lack of awareness that such symptoms can occur during food-induced allergic reactions and might not suggest anaphylaxis (in terms of cardiovascular compromise due to distributive shock).…”
Section: Discussionmentioning
confidence: 99%